Raz jeszcze o społecznej roli młodego pokolenia. Konteksty lokalne i globalne = Social Role of the Young Generation - Local and Global Contexts - Szafraniec, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Global research indicates the young as the biggest victim of the world economic crisis. Are they able then to become innovative force and important factor of modernization processes in Poland? There are many reasons which favour it. Any other generation of young Poles was so well educated and competitively open to new ideas and experiences as the contemporary one.What is more, no other generation was subjected to so invigorating stimulation - the period of system transformation, which meant not only many system changes but also Poland`s opening up to the world and global processes.
Keywords: młodzież; rola młodzieży; Polska